Mapping Workflows and Managing Knowledge - Kmetz, John L (Business Expert Press, 2012)
Ebook from IG Library ; This is a book that does what the title says, and is different from most business process mapping information in three key ways. First, it lets you capture all the knowledge that goes into a workflow in any kind of organization, including the most difficult kind of all, the tacit knowledge people bring to the job and carry in their heads. Second, it is simple, powerful, flexible, and easy to learn. Finally, this book does not require installing, learning, and applying a complicated program (sometimes requiring reorganization to support the software rather than the software supporting the organ.